Impact of high-intensity interval training on VO2 max among male collegiate ice hockey players in China: a pilot study - Yuan, Yandong; Geok, Soh Kim; Japar, Salimah (Human Resources Management Academic Research Society (HRMARS), 2024)
This pilot study evaluated the effects of high-intensity interval training (HIIT) on maximal oxygen uptake (VO2 max) among male collegiate ice hockey players in China. Using a cluster-randomized controlled trial (C-RCT) design, 18 participants aged 18 to 24 years were recruited and randomly assigned to either an experimental group (n = 9, receiving the HIIT intervention) or a control group (n = 9, receiving standard training). The intervention lasted two weeks, during which pre- and post-intervention assessments of VO2 max were conducted. The results indicated no significant changes in VO2 max within either group following the intervention, nor were there significant differences between groups. However, the HIIT group demonstrated a slight improvement in VO2 max compared to the control group, although this did not reach statistical significance. These findings suggest that a short-term HIIT intervention has a limited impact on VO2 max among collegiate ice hockey players. The study underscores the need for further research to explore the effects of varying intervention durations and training intensities on VO2 max in ice hockey players, which could significantly impact training regimens and enhance aerobic endurance, potentially revolutionising how we train athletes.